2022
DOI: 10.1007/s10557-021-07310-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Lipid-Lowering Therapies for Cardiovascular Prevention in Germany

Abstract: Purpose Novel pharmaceutical treatments reducing cardiovascular events in dyslipidaemia patients must demonstrate clinical efficacy and cost-effectiveness to promote long-term adoption by patients, physicians, and insurers. Objective To assess the cost-effectiveness of statin monotherapy compared to additive lipid-lowering therapies for primary and secondary cardiovascular prevention from the perspective of Germany’s healthcare system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Transition probabilities used to populate the model can be found in Table 1. Rates, hazard ratios, odd ratios, and probabilities with a different time horizon than 1 year were converted to 1-year probabilities, similar to previous peerreviewed methodologies and cost-effectiveness studies [20,21]. This widely used calculation considers the rate of patients progressing between disease states and the observation's follow-up period [21].…”
Section: Transition Probabilitiesmentioning
confidence: 99%
“…Transition probabilities used to populate the model can be found in Table 1. Rates, hazard ratios, odd ratios, and probabilities with a different time horizon than 1 year were converted to 1-year probabilities, similar to previous peerreviewed methodologies and cost-effectiveness studies [20,21]. This widely used calculation considers the rate of patients progressing between disease states and the observation's follow-up period [21].…”
Section: Transition Probabilitiesmentioning
confidence: 99%
“…A Markov model simulating the progression of CVD in dyslipidaemia patients was adapted from existing cost-effectiveness studies (Fig. 1) [23]. Patients transitioned between three distinct health states: "Alive without CVD", "Alive with CVD", and "Dead".…”
Section: Model Structurementioning
confidence: 99%
“…Every year patients were at risk of experiencing acute cardiovascular events (myocardial infarction, stroke, coronary revascularisation, unstable angina pectoris) and dying from CVD or non-CVD causes. Model structure adopted from Michaeli et al [23]. CVD cardiovascular disease…”
Section: Comparatormentioning
confidence: 99%
See 1 more Smart Citation
“…The international Reduction of Cardiovascular Events with Icosapent Ethyl–Intervention Trial (REDUCE-IT) showed that icosapent ethyl (IPE) 4 g/day when added to contemporary medical care including statin treatment reduced the risk of time to the first event of the primary composite outcome (cardiovascular death, nonfatal myocardial infarction [MI], nonfatal stroke, coronary revascularization, or unstable angina) by 25% (31% in the higher-risk, US subgroup), and reduced the risk of total (first and recurrent) events by 32% [6] , [7] , [8] . Further, IPE added to statin therapy is cost-effective compared with usual care in the US and Germany [ 9 , 10 ].…”
mentioning
confidence: 99%